2006
DOI: 10.1353/mcb.2006.0044
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Currency Pricing

Abstract: A special case of dollarization is analyzed: quotation of prices in dollars. The proposed explanation is price stickiness: when price adjustment is costly, firms prefer to fix their prices in a stable foreign currency in order to avoid frequent price changes. The proposed model demonstrates that there are often two Nash equilibria in an economy populated by symmetric firms: an equilibrium with uniform domestic currency pricing and one with uniform dollar pricing. Hence, foreign currency pricing may exhibit hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Parsons and Sato relate the pass‐through of East Asian exporters to their U.S. dollar invoicing behavior. See Friberg (1998) and Levina and Zamulin (2006) for a theoretical analysis of the third currency (i.e., U.S. dollar) pricing.…”
mentioning
confidence: 99%
“…Parsons and Sato relate the pass‐through of East Asian exporters to their U.S. dollar invoicing behavior. See Friberg (1998) and Levina and Zamulin (2006) for a theoretical analysis of the third currency (i.e., U.S. dollar) pricing.…”
mentioning
confidence: 99%
“…They show that highly dollarized banking system induces the central bank, as the last resort lender, to hold larger dollars reserves. Levina and Zamulin (2006) argue that in the presence of price rigidities, and in the absence of indexation mechanisms, dollar pricing might be an optimal strategy for a firm. Recently, Drenik and Perez (2017) have shown that dollar pricing of domestic sales might be a choice for firms that seek to hedge inflation risk in the absence of other inflationindexation mechanisms, particularly in the case of durable goods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in July 2007 a new law became effective banning -with some exceptions, in particular for real estate -domestic prices from being quoted in currencies other than the rouble (Moscow News, 2007). An analysis of the determinants of foreign currency pricing in Russia is provided by Levina and Zamulin (2006).…”
Section: Parallel Vehicle Financing and Investment Currency -The Continued Dominance Of The Us Dollarmentioning
confidence: 99%